PENGARUH TEMPERATUR PEMANASAN ASPAL DAN AIR PEMBENTUK ASPAL BUSA TERHADAP SIFAT ASLI ASPAL - Djoko Widajat (Direktorat Bina Teknik Jalan dan Jembatan, 2010)
Main material for foamed bitumen consists of asphalt and water. Asphalt properties which are viscous elastic and has a good cohesion create a support to become strong mixture. Clean water is one of the requirements to create foamed bitumen bubbles to meet the desired quality.. Furthermore, foamed bitumen quality is influenced by the heat temperature of the asphalt and precentage of water addition in foamed bitumen process. The quality of foamed bitumen is characterised by Expansion Ratio and Half Life. The paper analyses about the change of asphalt properties in foamed bitumen with WLB 10S (Wiertgen Laboratory - Scale for foam bitumen, 10S type) after addition of water. Asphalt is heated with variation of temperature from 160 - 180Â°C and variation of water addition from 1% to 5%. To know the change of asphalt properties, tests were conducted on foamed bitumen with water variation of the foamed bitumen from 0-4%. The tests included penetration, softening point, ductility and loss on heating (LOH) with time variaton test of 1 to 30 days. The result showed that penetration, softening point and LOH are almost similar to the original asphalt properties after water in foamed bitumen evaporated. After addition of wate, LOH parameter needs longer time to revert back to the original value. Based on the penetration Index, asphalt tends to have high temperature susceptibility in the beginning of test, however, it will change to be low temperature susceptible after days of testing period, Bitumen is still elastic (ductility > 140cm). To meet the criteria of expansion ratio and half time, high asphalt heating is not necessary. Key word : bitumen properties, foamed bitumen, Expansion Ratio, Half Life, asphalt Penetration Index